DREADD Activation of Pedunculopontine Cholinergic Neurons Reverses Motor Deficits and Restores Striatal Dopamine Signaling in Parkinsonian Rats - Sharma, Puneet K. (Neurotherapeutics, 2020)
The brainstem-based pedunculopontine nucleus (PPN) traditionally associates with motor function, but undergoes extensive degeneration during Parkinson’s disease (PD), which correlates with axial motor deficits. PPN-deep brain stimulation (DBS) can alleviate certain symptoms, but its mechanism(s) of action remains unknown. We previously characterized rats hemi-intranigrally injected with the proteasomal inhibitor lactacystin, as an accurate preclinical model of PD. Here we used a combination of chemogenetics with positron emission tomography imaging for in vivo interrogation of discrete neural networks in this rat model of PD. Stimulation of excitatory designer receptors exclusively activated by designer drugs expressed within PPN cholinergic neurons activated residual nigrostriatal dopaminergic neurons to produce profound motor recovery, which correlated with striatal dopamine efflux as well as restored dopamine receptor 1- and dopamine receptor 2-based medium spiny neuron activity, as was ascertained with c-Fos-based immunohistochemistry and stereological cell counts. By revealing that the improved axial-related motor functions seen in PD patients receiving PPN-DBS may be due to stimulation of remaining PPN cholinergic neurons interacting with dopaminergic ones in both the substantia nigra pars compacta and the striatum, our data strongly favor the PPN cholinergic–midbrain dopaminergic connectome as mechanism for PPN-DBS’s therapeutic effects. These findings have implications for refining PPN-DBS as a promising treatment modality available to PD patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-019-00830-4) contains supplementary material, which is available to authorized users.